2016
DOI: 10.2147/ijn.s102096
|View full text |Cite|
|
Sign up to set email alerts
|

Cerium oxide nanoparticles promote neurogenesis and abrogate hypoxia-induced memory impairment through AMPK–PKC–CBP signaling cascade

Abstract: Structural and functional integrity of the brain is adversely affected by reduced oxygen saturation, especially during chronic hypoxia exposure and often encountered by altitude travelers or dwellers. Hypoxia-induced generation of reactive nitrogen and oxygen species reportedly affects the cortex and hippocampus regions of the brain, promoting memory impairment and cognitive dysfunction. Cerium oxide nanoparticles (CNPs), also known as nanoceria, switch between +3 and +4 oxidation states and reportedly scaveng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…The earlier studies which were performed on understanding the antioxidant role of ceria were carried out in mammalian systems. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] In the present study, similar antioxidant activity was observed in adult fish PR neurons. This offers a new experimental animal tool to explore the long-term genetic effects of nanoparticle treatment.…”
Section: B Consilience Of the Role Of Ceria In Two Different Classessupporting
confidence: 82%
See 3 more Smart Citations
“…The earlier studies which were performed on understanding the antioxidant role of ceria were carried out in mammalian systems. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] In the present study, similar antioxidant activity was observed in adult fish PR neurons. This offers a new experimental animal tool to explore the long-term genetic effects of nanoparticle treatment.…”
Section: B Consilience Of the Role Of Ceria In Two Different Classessupporting
confidence: 82%
“…Recent in vivo studies has shown that in the brain, it promotes neurogenesis and abrogate hypoxia-induced memory impairment and protect rodent lungs from hypobaric hypoxia-induced oxidative stress and inflammation. 41,44 V. CONCLUSION Here, it has been shown that fortification of the adult photoreceptor culture with a single dose of nanoceria at the time of plating the cells significantly increases the survival of both rod and cone cells. Thus, this system could find applications in understanding the basic photoreceptor physiology as well as in high throughput drug screening against all kinds of age related retinal blindness.…”
Section: E Ceria Fortification For Survival In Extreme Environmentsmentioning
confidence: 90%
See 2 more Smart Citations
“…In the last decade, significant progress has been made in the synthesis and assembly of nanocrystals, and has allowed the control of their compositions, sizes, shapes,a nd functionalities. [1][2][3][4] More recently,e fforts have focused on the use of nonclassical nucleation and growth approaches, which allow the development of nanocrystals and nanoparticles with high complexity in terms of shape,composition, and enhanced functionality. [5][6][7] An important mechanism related to the non-classical approachi st he aggregation of nanoclustersa nd nanoparticles.…”
mentioning
confidence: 99%